Mapping Junior High School Education Facilities in Bogor: A Comprehensive Study - Adilah Mutiara Qanitah; Intan Nurul Aulia; Janthy Hidayat; Muhamad Yogie Syahbandar; Diniarrachma Kintan; Muhammad Shafik Ikhwan Bin Hamzah (BINA: JURNAL PEMBANGUNAN DAERAH, 2024)
Equitable distribution of educational facilities is very important because every citizen has the right to a decent and quality education as mandated in Law No. 24/2007 on minimum standards of educational facilities and infrastructure. Junior high school education is a bridge between elementary school and senior high school to university. This study and mapping of junior high school education facilities in Bogor Regency is intended to identify the distribution pattern and needs of school facilities and infrastructure at the junior high school level in Bogor Regency. The objectives of this study are 1) To identify the distribution pattern of junior high schools in Bogor Regency; 2) Identify the availability of junior high school facilities and infrastructure in Bogor Regency; and 3) Identify the availability of educational service facilities at junior high school level. Based on the data, analysis was conducted using qualitative and quantitative analysis methods. Data processing using the nearest neighbor technique (average nearest neighbor analysis) is to determine the distribution pattern of junior high school education facilities. Meanwhile, to determine the range of services using Geographic Information System (GIS) buffering analysis techniques. so that the results obtained, 1) The distribution pattern of junior high school facilities in Bogor Regency is clustered with a Critical Value (Z-Score) value of -21.829520, a Nearest Neighbor Ratio value of 0.658887 and an average distance between junior high school education facilities of 963.7 meters; 2) The range of services of junior high school facilities in Bogor Regency is dominated by road lanes.Keywords: study, mapping, distribution pattern, education facilities, junior high school.